Answer:
y - b = 1(x - a) - point-slope form
y = x + b - a - slope-intercept form
Explanation:
The point-slope form of an equation of a line:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lwv5ftdd36i4idvu50qxfdgwxhdby4wlt5.png)
The formula of a slope:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fc06wy5n2hf2a0hmyba6df4ibmxk1cn53a.png)
We have the points (a, b) and (a + 3, b + 3). Substitute:
![m=(b+3-b)/(a+3-a)=(3)/(3)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sb3pfakd1m9m8yvy9icf0mykwf8wqpqqza.png)
- point-slope form
Convert to the slope-intercept form: y = mx + b:
add b to both sides
- slope-intercept form